Proceedings of 3rd IEEE International Conference on Image Processing
DOI: 10.1109/icip.1996.560428
|View full text |Cite
|
Sign up to set email alerts
|

Phase watermarking of digital images

Abstract: A watermark is an invisible mark placed on an image that can be detected when the image is compared with the original. The mark is designed to identify both the source of an image as well as its intended recipient. The mark should be tolerant to reasonable quality lossy compression of the image using transform coding or vector quantization. Standard image processing operations such as low pass filtering, cropping, translation and rescaling should not remove the mark. Spread spectrum communication techniques an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
0
3

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(101 citation statements)
references
References 3 publications
0
98
0
3
Order By: Relevance
“…It was also found that the watermark survived lossy image compression using JPEG at normal settings (75% quality factor). Other methods exist that tolerate JPEG compression down to 5% quality factor [7,6,16,15]; work is underway to combine these with this approach. In addition, the mark is also reasonably resistant to cropping and could be recovered from a segment approximately 50% of the size of the original image.…”
Section: Cover Image Independent Schemementioning
confidence: 99%
See 1 more Smart Citation
“…It was also found that the watermark survived lossy image compression using JPEG at normal settings (75% quality factor). Other methods exist that tolerate JPEG compression down to 5% quality factor [7,6,16,15]; work is underway to combine these with this approach. In addition, the mark is also reasonably resistant to cropping and could be recovered from a segment approximately 50% of the size of the original image.…”
Section: Cover Image Independent Schemementioning
confidence: 99%
“…Many of the current techniques for embedding marks in digital images have been inspired by methods of image coding and compression. Information has been embedded using the Discrete Cosine Transform (DCT) [16,34,5,6] Discrete Fourier Transform magnitude and phase [15], Wavelets [16], Linear Predictive Coding [13] and Fractals [9,22]. The key to making watermarks robust has been the recognition that in order for a watermark to be robust it must be embedded in the perceptually signi cant components of the image [16,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Ruanaidh et. al projected watermarking in the frequency domain [26] through the amendment of the phase. The phase of a preferred coefficient of an N1×N2, DFT is adopted to insert a bit by adding a small 'δ'.…”
Section: B Transform Domain Watermarkingmentioning
confidence: 99%
“…If a transformed representation is used, it may be applied to the entire data (the whole image), or on a block-by-block basis. For images, watermarks have been applied to pixels [2], Fourier components [24], whole-image and block-based discrete cosine components [8,23,39], wavelet components [23], and Fourier-Mellin components [25,13]. One use of a transformed representation is to make the components of the data more independent; pixels in an image, for example, are highly correlated locally, which is not true of discrete cosine components.…”
Section: The Components Of a Watermarking Systemmentioning
confidence: 99%